The Effectiveness of Beneficial Plants in Oil Palm (Elaeis guineensis Jacq.) Area in Reducing the Attack Rate of Oil Palm Leaf-Eating Caterpillar (oplec) at PT. Socfindo Mata Pao Gardens. - Novita, Aisar; Merlyn Mariana; Windy Manullang; M. D. P. Sarumaha; Advent (Talenta Publisher, 2023)
The Effectiveness of Beneficial Plants in Oil Palm (Elaeis guineensis Jacq.) Areas in Reducing the Attack Rate of Oil Palm Leaf-Eating Caterpillars (OPLEC) At PT. Socfindo Pao Eye Gardens. The purpose of this study was to determine the effectiveness of beneficial plants in the oil palm plantation area (Elaeis guineensis Jacq.) in reducing the level of attack of the oil palm leaf-eating caterpillar (OPLEC) in PT Socfindo Kebun Mata Pao and to examine the factors that affect the level of Attack of the Palm Leaf Feeding Caterpillar (OPLEC) at PT Socfindo Kebun Mata Pao. This assessment was carried out from November to June 2022. The data collection method was carried out using primary and secondary data. The results showed that beneficial plants were more effective in reducing the attack rate of caterpillars that eat oil palm leaves in accordance with the SOP of PT. Socfindo Pao Eye Gardens. The factors that influence the increase in OPLEC pest attacks are climatic conditions (and physiological conditions.